The International Centre for Academic Integrity Canadian Consortium - Miron, Jennie; Clark, Angela; Seeland, Josh; Rouse, Ainsley (Canadian Perspectives on Academic Integrity, 2024)
Academic integrity serves as a critical foundation for learning in post-secondary institutions. However, educational organizations continuously face challenges that threaten efforts to uphold and promote academic integrity. While global collaborations focused on policies, procedures, activities, and research dedicated to academic integrity are valuable, it is equally important to recognize the unique contexts of groups of educational organizations, which are influenced by things like organizational culture, missions, geography, priorities, and specialties, to name a few. Consortiums that meet the specific needs of groups of organizations play a crucial role in this endeavour. This article will highlight one such consortium that is working to establish a Canadian presence in academic integrity and is affiliated with the International Center for Academic Integrity.